Survey on Various Testing Techniques and Strategies for Bug Finding (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Software testing is verification and validation process aimed for evaluating a program and ensures that it meets the required result. The main goal of software testing is to uncover the errors in software. So the main aim of test cases is to derive set of tests that have highest probability of finding bugs. There are many approaches to software testing, but effective testing of any software product is essentially a tough process. It is nearly impossible to find all the errors in the program. The major problem in testing is what would be the strategy that we should adopt for testing. Thus, the selection of right strategy at the right time will make the software testing efficient and effective. In this paper I have described software testing techniques which are classified by purpose.